Britannica all new kids' encyclopedia : what we know & what we don't - Lloyd, Christopher, 1968-; Luebering, J. E. (Britannica Books, 2020)
Presents a children's encyclopedia that offers information on a wide variety of topics that range from the birth of the universe to the future. Includes timelines; maps; notes on historical Game Changers and current experts; color photographs, illustrations, and infographics; an extensive glossary and index; and quizzes throughout.